Business and the Risk of Crime in China - Broadhurst, Roderic (ANU Press, 2011)
The book analyses the results of a large scale victimisation survey that was conducted in 2005-06 with businesses in Hong Kong, Shanghai, Shenzhen and Xi'an. It also provides comprehensive background materials on crime and the criminal justice system in China. The survey, which measured common and non-conventional crime such as fraud, IP theft and corruption, is important because few crime victim surveys have been conducted with Chinese populations and it provides an understanding of some dimensions of crime in non-western societies. In addition, China is one of the fastest-growing economies in the world and it attracts a great amount of foreign investment; however, corruption and economic crimes are perceived by some investors as significant obstacles to good business practices. Key policy implications of the survey are discussed.